Application of a Tele‐Ultrasound Robot During COVID‐19 Pandemic: A Feasibility Study. (11th June 2022) - Jiang, Wenli; Zhao, Xia; Gan, Tian; Liu, Ying; Luo, Shuilian; Zhu, Meifang; Chen, Sikai; Jiang, Yu; Wu, Meng
Abstract : Objective: To investigate the accuracy of ultrasonic diagnosis using the tele‐ultrasound robot in Leishen Shan Hospital. Method: Twenty‐two patients with novel coronavirus pneumonia from Leishen Shan Hospital voluntarily participated in this study. Their thyroids, neck vessels, hepatobiliaries and kidneys were scanned by both a tele‐ultrasound robot manufactured by Imabot Co., Ltd, Wuhan and conventional method. The ultrasound diagnosis of each patient was compared, and the ultrasound images obtained by the two methods were mixed together and double‐blindly diagnosed by an experienced ultrasound radiologist. Results: There were 44 positive lesions in 110 sites of 22 patients. Of which the two methods, 40 positive lesions were detected by the robotic method with 4 lesions missed (2 small polyps of gallbladder, 1 small hemangioma of liver and 1 small cyst of kidney) and 1 lesion misdiagnosed (normal carotid artery was misdiagnosed as carotid atherosclerotic plaque); 44 positive lesions were detected by conventional method with 1 small cyst of the liver was missed. There was no statistically significant difference in the accuracy rate between the robotic method and the conventional method using the chi‐square test of the four‐grid data ( P >.05). Conclusion: The application of tele‐ultrasound robot meets the standard of patient care during the pandemic. The method is feasible to provide adequate ultrasound information to diagnose common abdominal, vascular, superficial organ pathologies in patients with COVID‐19 with acceptable accuracy compared with a conventional ultrasound scan.